Deep brain stimulation of Hippocampus in Treatment-resistant Schizophrenia (DBS-HITS): protocol for a crossover randomized controlled trial - Chang Lu; Zhaolin Zhai; Kaiming Zhuo; Qiong Xiang; Jingxin Xue; Yuqing Zhao; Liqin Lang; Chunhong Shao; Liang Chen; Dengtang Liu (BMC Psychiatry)
Abstract Background Ventral hippocampus (vHipp) in schizophrenia is in a state of hyperactivity and hypermetabolism, where the glutamate/gamma-aminobutyric acid (GABA) imbalance leads to downstream dopamine hyperactivity in the midbrain-limbic system. High-frequency deep brain stimulation (DBS) can disrupt the abnormal synchronization of functional circuits and modulate local brain networks. Methods The DBS-HITS study is a crossover randomized controlled trial. DBS will be applied to bilateral vHipp in six patients. They will be randomly assigned to receive 3-month high-frequency active stimulation and then 3-month sham stimulation, or vice versa. After 6-month crossover trial phase, all participants will undergo personalized active stimulation. Researchers will assess clinical symptoms and neurocognition, collect EEG and PET-CT data during planned follow-ups. Adverse event will be researcher-assessed or participant self-reported throughout the trial. Discussion To our knowledge, the DBS-HITS study is the first hippocampal DBS randomized controlled trial for schizophrenia. The goal of the DBS-HITS study is to assess the efficacy and safety of hippocampal DBS in treatment-resistant schizophrenia (TRS) and to investigate its impact on hippocampal activity and glutamate/GABA metabolism. The study is expected to deepen our understanding of the effects and side-effects of neuromodulation in TRS to facilitate individualized DBS treatment. Trial registration NCT05694000 in ClinicalTrial.gov, registered on January 23, 2023.